Development of Potato-Based MSMEs “Ngaditatoes” in Ngadiwono Village, Tosari District, Pasuruan Regency: Study of Local Wisdom and Innovation - Safirna, Naja Alyya; Purnomo, Fellita Intan Putri; Finada, Cinta; Munawaroh , Hidayatul (Universitas Negeri Semarang, 2025)
This activity aims to analyze the potential of potato farming in Ngadiwono Village, examine the role of MSMEs in processing local agricultural products, and explore the use of digital marketing to increase the competitiveness of processed potato products. Methods in the community service program in Ngadiwono Village: first, conducting observations of MSME players who produce potatoes; second, delivering work programs; third, preparing the necessary materials and tools; fourth, explaining how to make products; and finally, developing a marketing process for innovated potato products. The results of this activity made residents interested in making and processing potatoes into Ngaditatoes products and marketing them.